1990
DOI: 10.1007/bf02075207
|View full text |Cite
|
Sign up to set email alerts
|

Significance of age, duration, obstruction and the dissection sign in intussusception

Abstract: A retrospective study of sixty consecutive cases of proven intussusception with attempt at contrast enema reduction was performed to evaluate currently proposed contraindications to such reduction. When patient age, duration of symptoms, presence of small bowel obstruction and presence of a dissection sign were considered alone, none of the findings indicated irreducibility. Our overall reduction rate was 72% with a complication rate of 3%. This is similar to previously reported series and we concur with more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…We were, however, unable to demonstrate that a longer duration of symptoms before an attempted enema reduction at the CH, with or without a prior attempt at a referring hospital, correlated with a significantly lower success rate or a greater incidence of complications. This finding is supported by other studies [14][15][16], although most authors have reported a negative impact of prolonged symptoms on outcome [6,[17][18][19][20][21][22]. If a longer duration of symptoms did have an effect on outcome that we were unable to detect because of a type-2 error, it would not likely have influenced our primary conclusion regarding repeat enema reduction in transferred patients because the symptom duration was comparable in the subjects who were transferred compared with those primarily managed at the CH.…”
Section: Discussionsupporting
confidence: 86%
“…We were, however, unable to demonstrate that a longer duration of symptoms before an attempted enema reduction at the CH, with or without a prior attempt at a referring hospital, correlated with a significantly lower success rate or a greater incidence of complications. This finding is supported by other studies [14][15][16], although most authors have reported a negative impact of prolonged symptoms on outcome [6,[17][18][19][20][21][22]. If a longer duration of symptoms did have an effect on outcome that we were unable to detect because of a type-2 error, it would not likely have influenced our primary conclusion regarding repeat enema reduction in transferred patients because the symptom duration was comparable in the subjects who were transferred compared with those primarily managed at the CH.…”
Section: Discussionsupporting
confidence: 86%
“…There are many clinical and imaging factors that contribute to the probability of a successful nonoperative reduction of intussusception [23,38,44,[46][47][48][49][50][51][52]. The longer the duration of symptoms (usually beyond 24 h), the lower the likelihood of successful nonsurgical reduction.…”
Section: Current Treatmentmentioning
confidence: 99%
“…We consider this appropriate because studies have shown that although the probability of reduction falls with longstanding intussusception, a successful reduction is still possible [23][24][25][26][27]. Research has also shown that although likelihood of success with free or trapped fluid is relatively low, success is still possible [28,29], and the vast majority (86%) of our respondents said they attempt reduction despite the presence of free fluid.…”
Section: Discussionmentioning
confidence: 84%